Encyclopedia of vibration - Braun, Simon; Ewins, D. J.; Rao, Singiresu S., 1944- (Academic Press, 2002)
The Encyclopedia of Vibration is the first resource to cover this field so comprehensively. Approximately 190 articles cover everything from basic vibration theory to ultrasonics, from both fundamental and applied standpoints. Areas covered include vibrations in machines, buildings and other structures, vehicles, ships, and aircraft, as well as human response to vibration. Each article provides a concise and authoritative introduction to a topic. The Encyclopedia includes essential facts, background information, and techniques for modeling, analysis, design, testing, and control of vibration. It is highlighted with numerous illustrations and is structured to provide easy access to required information. Key Features * Covers the entire field of vibration with 168 original articles written by leading international authorities * Presents concise overviews of key topics relating to mechanical, civil, aeronautical, and electrical engineering * Provides easy access to information through extensive cross-referencing, detailed subject index in each volume, and further reading lists in each article * Features hundreds of detailed figures and equations, plus color plate sections in each volume.
Keywords: Vibration -- Encyclopedias.; elektronické knihy; electronic books